2011
DOI: 10.5657/kfas.2011.0359
|View full text |Cite
|
Sign up to set email alerts
|

State of Aquaculture Management for Optimal Rearing of Eel Anguilla japonica

Abstract: This study was conducted to investigate the production, elver stocking, rearing facilities and rearing method of eel culture to determine aquaculture management conditions for optimal rearing of eel Anguilla japonica. The production of eel culture was evaluated by the proportion of eels from the main inland fin fish species production in Korea. Elver stocking was assessed by the elver stocking densities of pond and recirculation culture. Rearing facilities were investigated according to the rearing tank size p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In addition to price increases for A. japonica elvers, overall changes to eel culture, such as increases in the cost of raw materials for formula feeds (FFs), labor costs, and various expenses, have maintained constant pressure on eel farmers. In response, researchers have examined the use of FFs with no or reduced amounts of fish meal; how to lower the mortality rate; the development of functional feed additives; the application of high-density culture; and the relationships between rearing tank size and stocking density, between body weight and stocking density, and between body weight and daily feeding rate (Bae et al, 2008;Choi et al, 2008;Hwang et al, 2010;Son et al, 2011).…”
Section: Analysis Of Cholesterolmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to price increases for A. japonica elvers, overall changes to eel culture, such as increases in the cost of raw materials for formula feeds (FFs), labor costs, and various expenses, have maintained constant pressure on eel farmers. In response, researchers have examined the use of FFs with no or reduced amounts of fish meal; how to lower the mortality rate; the development of functional feed additives; the application of high-density culture; and the relationships between rearing tank size and stocking density, between body weight and stocking density, and between body weight and daily feeding rate (Bae et al, 2008;Choi et al, 2008;Hwang et al, 2010;Son et al, 2011).…”
Section: Analysis Of Cholesterolmentioning
confidence: 99%
“…In addition, these eels are common freshwater fish that have been cultured for a very long time (Liao, 2002). The eel aquaculture industry in these countries has been growing every year; for example, in Korea, production increased from 2,739 tons in 2000 to 6,766 tons in 2009 (Son et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Deelder (1984) proposed that European eel A. anguilla can adapt to the water temperature at a range from 0 to 30°C. The feeding activity in A. anguilla was stopped in less than 10°C and more than 38°C (Sadler, 1979) and less than 10°C and more than 36°C in A. japonica (Son et al, 2011). Tesch (2003) has shown that the optimum of water temperature for rearing of A. japonica elver is at a range of 24-28°C and 23-26°C for A. anguilla.…”
Section: Introductionmentioning
confidence: 99%